2021
DOI: 10.1021/jacs.1c00990
|View full text |Cite
|
Sign up to set email alerts
|

DCAF11 Supports Targeted Protein Degradation by Electrophilic Proteolysis-Targeting Chimeras

Abstract: Ligand-induced protein degradation has emerged as a compelling approach to promote the targeted elimination of proteins from cells by directing these proteins to the ubiquitin-proteasome machinery. So far, only a limited number of E3 ligases have been found to support ligand-induced protein degradation, reflecting a dearth of E3-binding compounds for proteolysis-targeting chimera (PROTAC) design. Here, we describe a functional screening strategy performed with a focused library of candidate electrophilic PROTA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
114
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(127 citation statements)
references
References 37 publications
5
114
0
Order By: Relevance
“…15 Finally, FKBPs are the key enabling adaptors for the clinically approved immunosuppressants FK506 and rapamycin as well as for several recently identied molecular glues. [16][17][18][19][20][21][22] Previously, we developed bicyclic [4.3.1] sulfonamides, [23][24][25][26][27] which mimic the core of the natural products FK506 and rapamycin, retain the anti-infective 23 and BMP-stimulating properties 6,10 of these natural products, but lack their immunosuppressive properties. However, the shallow FKBP binding site generally makes the development of ligands with drug-like properties challenging.…”
Section: Introductionmentioning
confidence: 99%
“…15 Finally, FKBPs are the key enabling adaptors for the clinically approved immunosuppressants FK506 and rapamycin as well as for several recently identied molecular glues. [16][17][18][19][20][21][22] Previously, we developed bicyclic [4.3.1] sulfonamides, [23][24][25][26][27] which mimic the core of the natural products FK506 and rapamycin, retain the anti-infective 23 and BMP-stimulating properties 6,10 of these natural products, but lack their immunosuppressive properties. However, the shallow FKBP binding site generally makes the development of ligands with drug-like properties challenging.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, finding new E3 ligase ligands to expand the toolbox of PROTAC technology is critical for further development of this field. Significant progress has been made in this regard in the last several years, resulting in the discovery of a number of new E3 ligase ligands[4], including some covalent ones that can recruit DCAF11[14], DCAF16[16], KEAP1[17b], RNF114[18], and RNF4[19] E3 ligases for PROTAC designing and protein degradation. Based on mathematical modeling[34] and previous studies[16–17, 18a, 39], covalent E3 ligase ligand-based PROTACs may outperform non-covalent E3 ligase ligand-based PROTACs due to better kinetics of ternary complex formation, and minimal perturbation of its endogenous substrates with low fractional occupancy of the recruited E3 ligase.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have also shown that cancer cells develop resistance to VHL-based bromodomain and extra-terminal domain (BET) PROTACs due to loss of CUL2 and to CRBN-based BET and CDK9 PROTACs because of CRBN loss[12]. Therefore, significant efforts have been devoted to finding new E3 ligase ligands, resulting in the discovery of ligands that can recruit AhR[13], DCAF11[14], DCAF15[15], DCAF16[16], KEAP1[17], RNF114[18], and RNF4[19] E3 ligases to degrade POIs. Identifying more E3 ligase ligands can further expand the toolbox, overcome the drug resistance, and potentially generate more potent and specific PROTACs.…”
Section: Introductionmentioning
confidence: 99%
“…Through this screen and using chemoproteomic approaches, they identified a covalent fragment KB02 as a recruiter for the substrate receptor DCAF16 of CUL4-DDB1 E3 ligases for TPD applications 8 . In a fourth successful example, Zhang et al performed a functional screen with a focused library of electrophilic PROTACs to discover a new recruiter that targets cysteines on DCAF11 9 . Thus, these studies have collectively showcased the utility of chemoproteomic approaches and cysteine-targeting ligands to expand the arsenal of E3 ligase recruiters for TPD applications.…”
Section: Main Textmentioning
confidence: 99%